Analisis Kualitas Layanan Berbasis Servqual Dan Pengaruhnya Terhadap Kepercayaan Serta Kepuasan Nasabah: Studi Pada Ksp. Pondok Arta Sejahtera - Ni Putu Kusuma Widanti; Adisti Maharani Krisna; Ni Kadek Pajar Kusumawati; Ida Ayu Agung Paramitaswari; Ni Wayan Septiawini (Universitas Triatma Mulya, 2025)
This study aims to analyze the influence of service quality and trust on customer satisfaction at Koperasi Simpan Pinjam (KSP) Pondok Arta Sejahtera, a member-based financial institution that plays an important role in promoting financial inclusion. Despite the social closeness among its members, KSP faces several challenges, including inconsistent service performance, suboptimal communication, and limited digitalization. This research is grounded in the SERVQUAL theory, which consists of five key dimensions of service quality: tangibles, reliability, responsiveness, assurance, and empathy. In addition, trust is understood as a fundamental factor for establishing long-term relationships between financial institutions and their customers. This study employs a descriptive quantitative method with a population of 575 customers. A sample of 86 respondents was obtained using a simple random sampling technique. Data were analyzed using multiple linear regression. The findings show that both service quality and trust have a positive and significant effect on customer satisfaction. The adjusted R² value of 0.620 indicates that the two variables explain 62% of the variation in customer satisfaction. However, the beta coefficients of the two variables suggest that their influence remains relatively weak. This implies that service quality and trust are already perceived as basic expectations by customers, so improvements in these areas do not substantially increase satisfaction levels. This study provides empirical contributions that have been relatively underexplored compared to the banking sector. Practically, KSP management needs to strengthen service innovation, improve communication quality, and consider additional variables such as customer value and service experience to enhance customer satisfaction.